Analyzing Short Story Writing Difficulties Among High School Students and Formulating Social Media-Based Solutions - Aini Fuji Insani; Yeti Mulyati; H Halimah; Rudi Adi Nugroho (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to analyze students' difficulties in writing short stories and formulate strategic solutions to bridge the gap between language skill demands and students' low literacy levels. Methods: This descriptive research with a qualitative approach involved 35 eleventh-grade students at SMAN 16 Bandung. Data were collected through interviews and questionnaires, followed by systematic analysis including data organization, specific data grouping, narrative description of student constraints, and drawing conclusions. Findings: The findings reveal that the primary root of students' difficulties in writing fiction lies in their low reading motivation. Specifically, empirical data shows that nearly 90% of the respondents experienced a deadlock in determining ideas and developing concepts. This lack of reading motivation directly results in limited vocabulary mastery, static plot development, and instances of plagiarism due to low independent imagination. Research Implications: These results provide crucial implications for pedagogical practices, urging educators to integrate innovative approaches. Solutions include utilizing social media inspirational stories as idea triggers, developing digital teaching materials, and implementing interactive learning methods combined with reward systems to establish a conducive learning environment. Originality: The originality of this study lies in conceptualizing the transition of social media typically viewed as a cause of low literacy into a strategic production modality for literary works. Rooted in the empirical finding of an 88% conceptual deadlock rate among students, this research offers a novel, evidence-based framework that redirects casual digital consumption toward bridging academic writing demands.